Enhancing Students Understanding of Hybridization in Organic Compounds through a Flipped Classroom Approach Combined with Game-Based Learning - Baroud, Najah; Aljarmi, Abtisam (Jurnal Pijar Mipa, 2025)
This study investigates how effective it is to combine flipped classroom and game-based learning strategies for teaching the intricate subject of hybridization in organic chemistry for the third semester of Chemistry Department students, Faculty of Education, University of Zawia, academic year 2024-2024. The research involves 60 participants, who are split into two groups: a main group (MG), which was taught using the combined approach of flipped classroom and game-based learning, and a comparison group (CG), which received conventional instruction. The MG was provided with pre-class instructional videos and PowerPoint slides, which were later reinforced through engaging activities in class, including competitive games aimed at applying the concepts learned. A post-test assessing memorization and understanding of hybridization concepts indicated that the MG surpassed the CG in both aspects. The MG obtained an overall score of 73.51% on memorisation questions, in contrast to the CG's 65.00%. The Percentage gap was 8.51%. For comprehension questions, the MG achieved an impressive 85.15%, while the CG managed only 48.95%. Percentage gap 36.2%.The results indicate that the combined strategies are effective in promoting a deep comprehension of the material. Moreover, qualitative responses from a questionnaire revealed a pronounced preference for the flipped classroom and game-based learning methods, as students noted enhanced engagement and understanding. This research underscores how innovative teaching methods can enhance the quality of chemistry education, stressing that interactive and adaptable learning environments are crucial for student success. Moreover, the study recommends employing such methods in chemistry education to enhance learning outcomes and boost student motivation.